Pola Penggunaan Obat Analgetik Antiinflamasi Nonsteroid di Pelayanan Farmasi IGD RSUD. Dr. Pirngadi Medan - Fidiah Suryaningsih; Darwin Syamsul; Peri Aisyah Zubaidi (Yayasan Penelitian dan Inovasi Sumatera, 2023)
Background: Pain is the main reason why patients come to the Emergency Room (IGD) with a prevalence of 78-86%. Non-steroidal anti-inflammatory Drugs (NSAIDs) are widely used to treat mild to moderate inflammatory pain. This study looked at the use of NSAIDs in the emergency room pharmacy services at Dr. Pirngadi Medan. Methods: This non-experimental, retrospective descriptive study was conducted at the Emergency Room Pharmacy Service at Dr. RSUD. Pirngadi Medan from January to June 2019. Results: Of the 11,257 NSAIDs used, mefenamic acid 500 mg three times a day (28.69%), diclofenac sodium 50 mg twice a day (24.96%), meloxicam 75 mg twice a day (2.29%), ketorolac injection 30 mg if needed (42.20%), meloxicam 15 mg suppository (0.07%), and proton suppository (1.79%) were given as needed. Conclusion: The use of NSAIDs in the emergency room at Dr. Pirngadi Medan in the January-June 2019 period had the correct indications, doses, drugs and patients.